Practice of Tracheostomy Decannulation among Neurosurgery Patients: Single Center Study - Thapa, Dinesh Kumar; Khadka, Ayesha; Prasai, Arzoo; Tamrakar Karki, Karuna (Eastern Green Neurosurgery, 2022)
Background: A tracheostomy is a surgical procedure in which trachea is opened below the larynx from which a tube is placed in trachea to facilitate mechanical ventilation, removal of tracheo-bronchial secretions and to protect upper airway. The aim of this study is to find out the current status of decannulation following institutional guideline.Materials and methods: A cross sectional study was done among patients in neurosurgery with tracheostomy who were successfully decannulated. This study was conducted in department of neurosurgery B&C Medical College Teaching Hospital, Jhapa, Birtamode. Total 47 patients were included in this study those underwent decannulation. Various demographic data including gender age diagnosis, days of tracheostomy and decannulation started day were recorded and entered in SPSS and version 20.Results: Among 47 patients, male were 81% (38) and females 19 %( 9). Road Traffic accident is the most common diagnosis 66% (31) among tracheostomy patients. The average days with Tracheostomy were 24. And after decannulation process, the successful tracheostomy closure in 83% (39) patients was achieved.Conclusion: Patients with tracheostomy tube could be decannulated successfully by following strict institutional guidelines, adequate medical and nursing care in a center with limited resources.